New peculiarities in angular distribution of Cherenkov radiation from relativistic heavy ions caused by their stopping in radiator: numerical and theoretical research; Journal of Physics: Conference Series; Vol. 357, iss. 1: RREPS-2011: Radiation from Relativistic Electrons in Periodic Structures - Fiks E. I. Elena Ivanovna (2012, 2012)
Title screen